Molecular characterization and antimicrobial susceptibilities of Clostridium difficile clinical isolates from Victoria, Australia. (August 2015) - Mackin, Kate E.; Elliott, Briony; Kotsanas, Despina; Howden, Benjamin P.; Carter, Glen P.; Korman, Tony M.; Riley, Thomas V.; Rood, Julian I.; Jenkin, Grant A.; Lyras, Dena
Abstract: Some Australian strain types of Clostridium difficile appear unique, highlighting the global diversity of this bacterium. We examined recent and historic local isolates, finding predominantly toxinotype 0 strains, but also toxinotypes V and VIII. All isolates tested were susceptible to vancomycin and metronidazole, while moxifloxacin resistance was only detected in recent strains. Highlights: Clostridium difficile is a nosocomial pathogen, with different strain types causing disease. We have generated a snap-shot of C. difficile strain types circulating in Victoria. The diversity of isolates in Victoria may differ from other parts of the world. Most strains were toxinotype 0, but toxinotypes V and VIII strains were also found. Strains were metronidazole and vancomycin sensitive; 2 were moxifloxacin resistant.